2005
DOI: 10.1210/en.2004-1452
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Regulation of Histamine H3 Receptor and VGF Messenger Ribonucleic Acid in the Arcuate Nucleus of the Siberian Hamster

Abstract: To survive winter the Siberian hamster has evolved profound physiological and behavioral adaptations, including a moult to winter pelage, regression of the reproductive axis, onset of daily torpor and increased capacity for thermogenesis. However, one of the most striking adaptations is the catabolism of intraabdominal and sc fat reserves contributing to the loss of up to 40% of body weight. These physiological and behavioral adaptations are photoperiodically driven, yet neither the site(s) in the brain nor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(133 citation statements)
references
References 62 publications
9
123
1
Order By: Relevance
“…Moreover, the high expression levels of H 1 R following the blockade of H 3 Rs plus the recent detection of the elevated transcription pattern of another major cellular stress factor, i.e., heat shock proteins (unpublished data) in the amygdala, supply convincing evidence that this limbic region and the increased expression of H 1 R, together with low H 3 R mRNA levels in another hibernating species (Barrett et al, 2005), may turn out to be key protective components for the different brain regions of patients with neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the high expression levels of H 1 R following the blockade of H 3 Rs plus the recent detection of the elevated transcription pattern of another major cellular stress factor, i.e., heat shock proteins (unpublished data) in the amygdala, supply convincing evidence that this limbic region and the increased expression of H 1 R, together with low H 3 R mRNA levels in another hibernating species (Barrett et al, 2005), may turn out to be key protective components for the different brain regions of patients with neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, high expression levels of H 3 R, especially in amygdalar areas as well as the cortex layers of the hamster treated with 3-NP, appear to be consistent with species-specific responses as shown by an up-regulation of this subtype in striatum of stressed rats (Ito et al, 1999) as compared with a down-regulation in diencephalic areas of other pathological states such as status epilepticus in the rat (Jin et al, 2005). Moreover, even environmental-related stressful conditions tend to play a determinant role on the transcriptional activity of this subtype as confirmed by the varying photoperiodic effects accounting for a down-regulating trend of H 3 R mRNA levels in the same brain region of another species, the Siberian hamster (Barrett et al, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…Under the control of photoperiod this species naturally becomes obese in the summer, but then enters a catabolic state in which it becomes hypophagic during winter and catabolises abdominal fat reserves such that it loses up to a third of its total body weight [29,30,31]. Barrett et al [32] found that VGF mRNA expression is dramatically regulated in relation to this body weight cycle, with significantly higher hypothalamic expression in the winter catabolic state as compared to the summer anabolic state (fig. 2) [32].…”
Section: Vgf-derived Peptides In a Seasonal Model Of Altered Energy Bmentioning
confidence: 99%
“…Barrett et al [32] found that VGF mRNA expression is dramatically regulated in relation to this body weight cycle, with significantly higher hypothalamic expression in the winter catabolic state as compared to the summer anabolic state (fig. 2) [32]. This upregulation is restricted to the dorsomedial posterior arcuate nucleus (dmpArc), a region of the hamster hypothalamus where a number of other genes related to retinoic acid, histaminergic and serotoninergic signaling have also been documented to change in relation to season [32,33,34].…”
Section: Vgf-derived Peptides In a Seasonal Model Of Altered Energy Bmentioning
confidence: 99%
See 1 more Smart Citation